Перші знахідки борошнисторосяного гриба Sawadaea bicornis (Wallr.) Homma на Acer velutinum Boiss. в Україні - Heluta, V.P.; Dzhagan, V.V.; Senchylo, O.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2016)
Information on the first records of Sawadaea bicornis (Wallr.) Homma on the ornamental maple (Acer velutinum Boiss.), an introduced species in Ukraine, is given. For the first time, the fungus was found in 2014 in Academician O.V. Fomin Botanical Garden (Kyiv) and was observed here in the next year. Infection of A. velutinum was not significant. Mycelium of the fungus was clearly visible on the upper side of leaves as diffuse gray spots. Fruiting bodies were formed. These records are new for both Ukraine and Europe. It is suggested that this finding is an evidence of a possibility of local races of powdery mildews parasitizing the native hosts to infect the closely related introduced plants.